2011
DOI: 10.1016/j.molcel.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A Common Telomeric Gene Silencing Assay Is Affected by Nucleotide Metabolism

Abstract: Telomere-associated position effect variegation (TPEV) in budding yeast has been used as a model for understanding epigenetic inheritance and gene silencing. A widely used assay to identify mutants with improper TPEV employs the URA3 gene at the telomere of chromosome VII-L that can be counter-selected with 5-fluoroorotic acid (5-FOA). 5-FOA resistance has been inferred to represent lack of transcription of URA3 and therefore to represent heterochromatin-induced gene silencing. For two genes implicated in telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
96
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 39 publications
4
96
0
Order By: Relevance
“…Additionally, some Y9 elements are transcribed, a fact that is inconsistent with Sir protein-mediated repression of all Y9 elements (Fourel et al 1999;Pryde and Louis 1999). In addition to these discrepancies, metabolic reporters are not biologically neutral, and some complexity regarding these reporters has emerged (Rossmann et al 2011;Takahashi et al 2011). For example, DOT1, SWI4, and ARD1, all of which abrogate H3K79 methylation, had been implicated in telomeric silencing, as assayed by the URA3 reporter at artificial telomeres.…”
mentioning
confidence: 99%
“…Additionally, some Y9 elements are transcribed, a fact that is inconsistent with Sir protein-mediated repression of all Y9 elements (Fourel et al 1999;Pryde and Louis 1999). In addition to these discrepancies, metabolic reporters are not biologically neutral, and some complexity regarding these reporters has emerged (Rossmann et al 2011;Takahashi et al 2011). For example, DOT1, SWI4, and ARD1, all of which abrogate H3K79 methylation, had been implicated in telomeric silencing, as assayed by the URA3 reporter at artificial telomeres.…”
mentioning
confidence: 99%
“…It was originally identified as a high copy disruptor of telomeric silencing in Saccharomyces cerevisiae (10). Two recent studies have demonstrated that the role of Dot1 in heterochromatin gene silencing might be overestimated in the original URA3 telomere silencing reporter assays in yeast (11,12). Nevertheless, Dot1 participates in heterochromatin formation through competing with Sir3 for a binding site on histone H4 (13).…”
mentioning
confidence: 99%
“…1 are metabolic in nature and Gdh1 is a metabolic protein, we further evaluated Gdh1's role in silencing through independent assays. Recent studies showed that 5-FOA-based telomeric silencing assays could give false-positive results for mutants that elevate ribonucleotide reductase (RNR) activities (37,38). One way to eliminate the confounding effect is to inhibit RNR activity with 10 mM hydroxyurea (HU) (37).…”
Section: Gdh1 Regulates Recruitment Of Sir Proteins To Silent Chromatmentioning
confidence: 99%
“…Recent studies showed that 5-FOA-based telomeric silencing assays could give false-positive results for mutants that elevate ribonucleotide reductase (RNR) activities (37,38). One way to eliminate the confounding effect is to inhibit RNR activity with 10 mM hydroxyurea (HU) (37). Adding HU did not rescue the 5-FOA sensitivity of gdh1Δ TELV-R::URA3, suggesting that the 5-FOA readout is likely a true reflection of gdh1Δ's silencing defect ( Fig.…”
Section: Gdh1 Regulates Recruitment Of Sir Proteins To Silent Chromatmentioning
confidence: 99%